The Pursuit of Empowerment through Social Media: Structural Social Capital Dynamics in CSR-Blogging - Fieseler, Christian 1978-; Fleck, Matthes 1981- (2013)
With the emergence of participative social media, the ways in which stakeholders may interact with companies are changing. Social media and Web 2.0 technologies change gatekeeping mechanisms and the distribution of information. In consequence, organizations must realize that they are structurally embedded in online networks of interconnected and equitable actors. In this paper, we analyze how this change in today’s information and communication technologies may affect Corporate Social Responsibility (CSR) action. We utilize social network analysis to investigate the CSR blogs of three IT firms: Google, Hewlett-Packard, and Intel. The analysis reveals that their Internet-enabled social networks exhibit patterns of power law distribution and an uneven distribution of structural social capital among the actors involved, especially on the corporate side, which fails to fully engage with the network. We conclude by indicating the research implications of shifting social capital dynamics and by deriving implications for management and practice.
Keywords: Web 2.0; Structural social capital; Social Network Analysis; Social Media; Online communication